(untitled) (Journal of the College of Basic Education, 2022)
Muhammad bin Al-Rashid was a politician of the first order, and he knew what he wanted and possessed his acumen and intelligence. Therefore, he appointed Muhammad bin Faisal as ruler of Riyadh as a result of the circumstances that passed on the second Saudi state, as well as as a result of his fear of public opinion turning against him. Ibn Al-Rashid mentioned the eligibility of the Al Saud to rule They ruled Najd for nearly a century and a half, so it was not easy for the inhabitants of the Arabian Peninsula to accept a new ruler other than the Al Saud family, especially after things turned to him and Prince Abdul Rahman became a homeless person in the desert.